Contacts and Contrasts in Cultures and Languages - Lewandowska-Tomaszczyk, Barbara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume provides descriptions and interpretations of social and cognitive phenomena as well as processes that emerge at the interface of languages and cultures in the context of contrastive and contact linguistics and media discourse. Different contexts are explored with rich empirical findings and authentic exemplifying materials. The book includes fifteen papers, divided into three parts. Part 1 addresses conceptual reflection on languages and cultures in contact and contrast, while Part 2 focuses on contact linguistics and borrowing. Part 3 discusses cultural and linguistic aspects of media discourses.
I am Not a Gobi Girl! Observations on Cultural Similarities and Differences Based on Four Years of Fulbright Fellowships in Poland, Latvia, and Outer Mongolia -- Meaning, Perception, and Culture in International Business Discourse: A Theoretical Analysis of Potential Conflicts -- Expressing Modality in Commercial Agreements and Contracts - The Analysis of Polish-English Parallel Texts -- Culture Diversity in English - Arabic Proverbs -- Ernest Hemingway's "Mr. and Mrs. Elliot": A Narrative of a Failed Romance -- (Un)successful Communication: Sex-based Differences and Contrasts -- Similarities and Contrasts in Multisensory Metaphorical Conceptualisations of Memories in Polish and English -- Metaphors of Pride in Polish and English - A Corpus-based Study -- Blending In: Hybridity, Identity and Creolization -- The Presence of Loanwords of Nahuatl Origin in the Press of Veracruz, Mexico -- Contrasting News Values in Newspaper Articles and Social Media: A Discursive Approach to the US Ruling on Same-Sex Marriage -- A Corpus-assisted Critical Discourse Analysis of "migrants" and "migration" in the British Tabloids and Quality Press -- Linguistic Differences in Headlines: Comparison between Korean and American Newspapers -- Well-being and Collective Identity in Cross-cultural Contexts -- The Phenomenon of Global English in the World of Interactive Online Entertainment.
Keywords: Intercultural communication; Psycholinguistics; Communication; Linguistics -- Methodology; Intercultural Communication; Psycholinguistics and Cognitive Lingusitics; Media and Communication; Research Methods in Language and Linguistics